2003
DOI: 10.1103/physrevb.68.054428
|View full text |Cite
|
Sign up to set email alerts
|

Intrinsic and hysteresis properties of FePt nanoparticles

Abstract: This comprehensive study examines the effect of particle size and atomic ordering on the intrinsic and hysteresis properties of FePt nanoparticles embedded in a carbon matrix formed by annealing sputtered FePt/C multilayer precursors. Structural studies show a transformation from the magnetically soft to the tetragonal FePt phase dependent on the annealing conditions. The magnetic properties scale as a function of particle size. The coercivity depends, in part, on the vol % of carbon and develops with annealin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
23
0

Year Published

2005
2005
2009
2009

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 60 publications
(28 citation statements)
references
References 30 publications
3
23
0
Order By: Relevance
“…It shows a main peak at 276 kOe and a shoulder at 304 kOe. However, the best fitting of the spectra is obtained by superimposing to a main contribution (sextet ϕ, H hf = 275 kOe, E Q = 0.04 mm/s) the following two sextets: -sextet ψ (H hf = 305 kOe, E Q = 0.00 mm/s) which can be attributed to the cubic FePt phase [6] and -sextet τ (H hf = 269 kOe, E Q = 0.29 mm/s) which can be interpreted as due to the tetragonal FePt phase [6,7]. Accordingly, a careful inspection of the corresponding XRD spectrum (Fig.…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…It shows a main peak at 276 kOe and a shoulder at 304 kOe. However, the best fitting of the spectra is obtained by superimposing to a main contribution (sextet ϕ, H hf = 275 kOe, E Q = 0.04 mm/s) the following two sextets: -sextet ψ (H hf = 305 kOe, E Q = 0.00 mm/s) which can be attributed to the cubic FePt phase [6] and -sextet τ (H hf = 269 kOe, E Q = 0.29 mm/s) which can be interpreted as due to the tetragonal FePt phase [6,7]. Accordingly, a careful inspection of the corresponding XRD spectrum (Fig.…”
Section: Resultsmentioning
confidence: 98%
“…In particular, it is reasonable to assume that evaporated 57 Fe diffuses into surface regions of the FePt hard film giving raise to superparamagnetic iron (singlet α 1 ) due to its coalescence in low density regions, and 57 Fe-containing FePt particles characterized by a large grain size distribution (τ (1,2) and δ contributions). The doublet δ can be due to FePt small particles showing a superparamagnetic behaviour and the τ 1 , τ 2 components can be ascribed to FePt larger particles showing a collapsing H hf which decreases from the value typical of the tetragonal phase [7,9].…”
Section: Resultsmentioning
confidence: 99%
“…They attract much attention as a promising material for hyperthermia [27][28][29]. With decreasing particle size in FePt nanoparticles C T [30,31] and c H [30] decrease. The Curie temperature of 4 nm FePt nanoparticles is about 200-300 K lower than that of bulk FePt (750 K) [31].…”
Section: Resultsmentioning
confidence: 99%
“…In order to achieve these requirements, several studies were reported. [6][7][8][9][10][11][12][13] For example, a small grain and a high perpendicular magnetic anisotropy L1 0 phase has been observed on FePt films using multilayer deposition techniques and a rapid thermal annealing ͑RTA͒ method. In general, an annealing temperature of about 350-550°C is required.…”
Section: Introductionmentioning
confidence: 99%
“…In general, an annealing temperature of about 350-550°C is required. [10][11][12][13][14] Ion-irradiation has been applied widely to modify the magnetic properties in magnetic thin films or superlattices. He-ion irradiation was used to control the degree of chemical ordering of FePd, Co/ Pt, and FePt films.…”
Section: Introductionmentioning
confidence: 99%